The power of authority and the Montessori teachers’ (in)ability to learn – research intervention report - Jarosław Jendza (Problemy Wczesnej Edukacji)
The article concentrates on the issue of Montessori teachers’ attitude towards pedagogical knowledge they develop during different forms of training. The analysis presented in the text is based on quasi-experiment rooted in Critical Realism research paradigm. Eighty-two Montessori teachers participated in a workshop and were asked to comment on eight different quotes. Half of them knew that these extracts had been taken from the publications by Maria Montessori and the other half did not have that knowledge. As a result, the first group of teachers formulated numerous critical remarks whereas the other one concentrated on positive interpretations. This experiment might shed some light on the power of authority and limitations to transform teachers’ implicit pedagogical presuppositions. The teachers that took part in this experiment were provided with the opportunity to problematize their personal teaching theories.